POLA KOMUNIKASI PERSUASIF ASATIDZAH TERHADAP MOTIVASI BELAJAR SANTRI DI PONDOK PESANTREN AISYIYAH IMADUL BILAD TAKHASUS TAHUN 2019 - Annur, Kamala Farida; Songidan, Junaidi; Nur, Muhammad (DECODING: Jurnal Mahasiswa KPI, 2020)
AbstractCommunication is an important thing for every human life. As social beings who always interact with other people, we always need communication, either to conveymessages or receive messages from other people, either through writing or in person. Inthis case, communication is also very much needed in Islamic boarding schools, becausein the world of education communication cannot be separated, either to build students'motivation to learn or others.This type of research is field research, namely researchconducted in real life. Methods in data collection that researchers use are methods ofobservation, interviews, documentation. The available data is analyzed, then presentedsystematically and then conclusions are drawn.The factors that come from the studentsare awkwardness, shame, fear, and loss of focus. Factors in the form of both the cottageenvironment and the family environment. The supporting factors are the asatidzah state,the familiarity between the asatidzah and the students, and the sufficient time intensity.